Characterization, density and distribution of mechanoreceptor sensillas on cephalic scales of two species of snakes inhabiting different aquatic environments (2017)
For the first time in the neotropics we describe the morphology and analyze the distribution and density of mechanoreceptor sensillas located on the cephalic scales of the aquatic snakes Helicops pastazae and Helicops angulatus. Both species studied here differ in their ecological habitats, i.e. H. pastazae occupy preferably lotic systems, while H. angulatus prefer lentic systems. We combined scanning electron microscopy and histological techniques to describe the external and internal morphology of these mechanoreceptors. Scanning Electron Microscopy (SEM) showed the sensillas as prominent structures with concentric rings of keratine around it; while histological slides showed an evident reduction in the keratin layer over these sensillas and a particular organization of the sensory cells below it. Images of high-depth-of-field photography allowed us to determine the spatial distribution and to calculate the density of sensillas for both species and for males and females. In half of the scales analyzed, we found a higher density of sensillas on the cephalic scales of H. pastazae in comparison to H. angulatus. We also found a higher density of sensillas in males compared to females in both species and in most of the scales analyzed. Finally, we observed a higher density of sensillas on the scales positioned anteriorly compared to those in a posterior region of the head. We conclude that scale sensillas in both species of Helicops studied here are mechanoreceptors under a morphological approach and that the differences in size and densities of the sensillas between both species could be explained by the ecological and behavioral differences between both species, and also between males and females